Person-centered care for people with aphasia: tools for shared decision-making - Hinckley, Jacqueline; Jayes, Mark (Frontiers in Rehabilitation Sciences, 2023)
Shared decision-making is a fundamental aspect of person-centered care, and can and should be part of many different aspects of the rehabilitation process.Communication disabilities like aphasia, which affects people's ability to use and understand spoken and written language, can make shared decision-making especially challenging to the resources and skills of rehabilitation practitioners. The purpose of this narrative review is to provide a comprehensive description of tools that can support successful shared decision-making with people with aphasia in the rehabilitation environment. These tools and strategies are appropriate for use by physicians, nurses, social workers, physical therapists (also referred to as physiotherapists), occupational therapists, and other service or care providers. The important role of speech-language pathologists as consultants is also described. Case scenarios throughout the paper illustrate the application of recommended tools and strategies along with best practices.